1993
DOI: 10.3109/15513819309048221
|View full text |Cite
|
Sign up to set email alerts
|

Renal Developmental Arrest in Sudden Infant Death Syndrome

Abstract: Investigations linking sudden infant death syndrome (SIDS) and type II intrauterine growth retardation (IUGR) have thus far failed due in part to technical limitations. Recently developed stereological methods for the unbiased estimation of total nephron number in the human kidney are capable of detecting deviations from normal values of greater than 10%. We compared the total number of nephrons in the kidneys of 24 SIDS victims with those from 16 controls with the same age range. Mean nephron number was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 17 publications
2
37
1
2
Order By: Relevance
“…Hinchliffe et al [2,3] showed that glomerular number was reduced in infants suffering from IUGR [2] and that the glomerular number was significantly reduced in SIDS infants of both NBW and LBW [3]. Our mean glomerular number for 13 non-SIDS NBW infants was 653,997, which is considerably less than Hinchliffe et al's [3] 903,000 and that found by Gilbert et al [6], who reported a mean number of 975,000 glomeruli.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Hinchliffe et al [2,3] showed that glomerular number was reduced in infants suffering from IUGR [2] and that the glomerular number was significantly reduced in SIDS infants of both NBW and LBW [3]. Our mean glomerular number for 13 non-SIDS NBW infants was 653,997, which is considerably less than Hinchliffe et al's [3] 903,000 and that found by Gilbert et al [6], who reported a mean number of 975,000 glomeruli.…”
Section: Discussioncontrasting
confidence: 78%
“…We also excluded cases in which the individual had suffered a chronic illness at any time, as it is also not known how these illnesses may affect normal organogenesis. Therefore, the infants used in the control group of both this study and that by Hinchliffe et al [3] were very similar. Even so, statistical comparison of the present non-SIDS NBW data to the non-SIDS NBW data from Hinchliffe et al [3] shows that there is a statistically significant difference between the two groups ( p Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The IUGR animals were defined using parameters previously described in infants (Battaglia and Lubchenco, 1967). Using design-based, unbiased stereological techniques (Hinchliffe et al, 1993), whole kidney and cortex volume, total glomerular number and glomerular volume were determined. Functional tests, including amniotic and allantoic fluid analysis, inulin/paraaminohippuric acid and fractional excretion of electrolytes, have already been performed (Holdstock, 1995), and were correlated to the stereological findings of the kidneys.…”
Section: Methodsmentioning
confidence: 99%
“…In man, IUGR has been defined when an infant is born at a birth weight significantly below (10 th percentile) the mean for gestation, irrespective of any clinical features shown (Battaglia and Lubchenco, 1967). In spite of the absence of macroscopic organ defects, stereological techniques have revealed important micro-anatomical deficiencies and, in particular, glomerular number in the kidneys of infants suffering from IUGR and SIDS (Hinchliffe et al, 1992(Hinchliffe et al, , 1993. Little is known about normal renal organogensis in the horse and stereological techniques are novel in their application to equine tissue.…”
Section: Introductionmentioning
confidence: 99%